Inter-Institutional Acadeimc Alliances - When, Why, Who, and How? - Moxley, Virginia (Institute for Academic Alliances, 2009)
Universities are collaborating to deliver online academic programs that capitalize on their technological and human capacities. Inter-institutional programs have the advantages of distributed risks, increased reach, and greater depth and scope. This paper focuses on the attributes of administrative teams that successfully lead such alliances and the strategies they employ to create sustainable programs.
Keywords: Institute for Academic Alliances; Inter-institutional programs; Alliance administration; Online education; Academic consortia; Higher education administration; Great Plains IDEA